Sposób postrzegania osób z wadą wymowy przez społeczeństwo – badania własne - Knychalska-Zbierańska, Monika (Logopedia Silesiana, 2015)
The article presents the image of people with a speech impediment in the perception of the society. Numerous observations and studies indicate that the perception of children suffering from speech difficulties correlates with their low self-esteem. The consequences of it are numerous difficulties, connected to school on the one hand, and to the establishment of relationships, emotional ties and social skills on the other. Speech development influences the development of thinking, and thus it is related to the advancement with respect to school and professional careers. Communication difficulties often close the door to a “better world” for children – and later adults. Therefore, the research conducted has been designed to examine how speech therapists’ patients are seen by others. Looking into this problem from this perspective enables one to individualise a therapy in such a way that the young patients are entering the stage of schooling with increased self-confidence.